Le travail en équipe en école primaire : une autonomie sous contrainte - Cécile Roaux (Éducation et Socialisation)
This article examines the paradox induced by the teamwork “injunction” in a French Primary School, such as it has remained both without principal, highly focused on the classroom and in a system centralized. This (pseudo) location of the school system is studied both from the Supervision members’ point of view (hierarchy represented by Ministerial Cabinet and political staff) and from the « field members »’ viewpoint. The mistrust that this “imposed” collective work generates among teachers, finally turns away from truly collaborative work and leads to withdrawal and team conflicts, tensions between a delegitimized – but ambiguous – “bureaucracy” and “anarchy” fuelled by organizational contradictions in a period of repository change.